Fator de necrose tumoral alfa (TNF-α) inibe a formação do biofilme de Candida albicans - Xerez, Morgana Ramos Martins (2016)
The aim of this study was to investigate the activity of TNF-α against Candida albicans biofilm. Therefore, week biofilm producer (49BMv and 51BMv) and strong biofilm producer (ATCC 10231 and CEMM 01.05.006) strains of C. albicans were incubated in RPMI medium in 96-well plates at 35 °C for 48 or 96 hours in order to assess biofilm formation and mature biofilm, respectively, in the absence or presence of different concentrations of TNF-α (0.1, 0.5, 1, 10, 20 and 40 ng/ml). TNF-α was added during preparation of the biofilm to assess its effect on biofilm formation or after 48 hours of culture for evaluation in mature biofilm. After incubation, the metabolic activity was assessed using XTT reduction assay. The minimum inhibitory concentration (MIC) of TNF-α against C. albicans was evaluated by broth microdilution technique according to Document M27-A3, recommended by CLSI, using the concentrations 0.5, 1, 10 and 20 ng/mL. An analysis of the hyphae/blastoconidia ratio in biofilm was performed using optical microscopy by couting of filamentous (hyphae and pseudo-hyphae) and yeast cells and then a formula which allowed visualization of the relationship between the amount of filamentous and other structures was applied. The results indicated that TNF-α showed a significant inhibition of biofilm formation in a dose-dependent way and a discrete mature biofilm inhibition. In addition, the analysis of hyphae/blastoconidia ratio showed a statistically significant reduction in the number of filamentous forms in biofilm formation in the presence of TNF-α. However, the growth of C. albicans in planktonic form was not affected by any of the TNF-α concentrations used. These results indicate that TNF-α inhibits the formation of C. albicans biofilms, probably through the suppression of filamentation, a crucial step in biofilm formation.